Reception of Dietary and Other Health-Related Lifestyle Advice to Address Non-communicable Diseases in a Primary Care Context: A Mixed-Method Study in Central Argentina - Sánchez Urbano, Raúl E.; Paredes, Ariel; Vargas Chambi, Frank R.; Guedes Ruela, Pedro; Olivares, David E. V.; Souza Pereira, Benicio T.; Pacheco, Sandaly O. S.; Pacheco, Fabio J. (Frontiers in Nutrition, 2021)
An effective way to address risk factors for non-communicable chronic diseases (NCD) and reduce healthcare costs is by using sound health-related advice (HRA) to promote healthy lifestyle habits. In Argentina, however, few studies have examined the context in which HRA advice is communicated and undertaken by patients at the primary care level. In this study, we assessed the reception of HRA using a mixed-method approach in a central area of Argentina. A total of 1044 participants from the community were contacted and sociodemographic characteristics, health-related lifestyle factors, and medical history were collected. A calendar with health messages was provided to participants and its usage was assessed after one year. Additionally, semi-structured interviews were conducted with 34 patients attending a local primary healthcare center. The results show that HRA was given more frequently to individuals with a higher mean age, lower educational level, and to females. Participants with a chronic health condition are at a higher chance of receiving advice to reduce salt intake and maintain a healthy weight. Dietary advice is offered along with other lifestyle recommendations. The use of alcohol and tobacco is usually addressed together. HRA was primarily received in the context of an NCD diagnosis and advice was directed, especially, to risky behaviors. The HRA to increase the intake of fruits and vegetables, was mentioned less frequently. Patients at the healthcare center greatly appreciated receiving an HRA, especially when given in a tailored, written, and detailed form, and acknowledged its importance to prevent or control a chronic health condition as part of the medical treatment but showed concern regarding the ability to fully incorporate the advice. Lifestyle recommendations are highly appreciated by patients but are still underutilized since they are offered mostly in the context of illness. The health calendar was shown to be useful to complement health intervention programs at the community level. The findings of our study underscore the acknowledged value of HRA by participants to tackle risk factors of chronic diseases. If properly used HRA constitutes a simple and highly valued tool to help address patient's needs to prevent and control NCD in Argentina.